MOTIVATING STUDENT’S TO SPEAK ENGLISH THROUGH FUN ROLEPLAY METHOD AT THE 8TH GRADE OF SMP AHMAD YANI MAKASSAR - Muhammad Fajri Fadli; Baso Jabu; Samtidar Samtidar (State University of Makassar, 2022)
This research is aims to discovered whether the use of fun roleplay can motivate the 8th grade students of SMP Ahmad Yani Makassar to speak English. This research is an experiment study using a pre-experimental design, namely one-shot case study. The techniques that used are data analysis, data reduction, data presentation, and drawing conclusions. Based on the results of the research, it is found that the application of the fun role play method has been carried out in accordance with the steps in fun role play. The steps for playing this role are as described, starting from the teacher choosing the theme to be played and then let the student pick their own theme after that, preparing a script or storyline, explaining the techniques and rules in the game, dividing or choosing the role of each student, telling while setting the first scene of discussion and evaluating learning. Based on the findings, it is found that the used of fun roleplay methods can increase students motivation to learn to speak English better than before.Keyword: Fun Rolepaly, Method, Motivating